Shallow water sea slugs (Gastropoda: Heterobranchia) from the Andhra Pradesh, India - J.S. YOGESH KUMAR; ARYA SEN; C. RAGHUNATHAN; C. VENKATRAMAN (Smujo International, 2024)
Abstract. Kumar JSY, Sen A, Raghunathan C, Venkatraman C. 2024. Shallow water sea slugs (Gastropoda: Heterobranchia) from the Andhra Pradesh, India. Nusantara Bioscience 16: 154-168. The current manuscript explores the initial underwater survey findings, revealing 19 heterobranch species across 10 genera, 6 families, 2 suborders, one order, and one superorder within the Visakhapatnam coast of Andhra Pradesh, India. While, the heterobranchs fauna of Andhra Pradesh has been studied by several authors, it has been observed that underwater surveys to discover this marine group are lacking from the region, and therefore, the present study has been done. These species from the study site include Coryphellina exoptata, Pteraeolidia semperi, Dendrodoris krusenstenii, Doriprismatica atromarginata, Glossodoris sp. cf. cincta, G. rufomarginata, Goniobranchus alius, G. setoensis, G. fidelis, G. trimarginatus, Hypselodoris bullockii, H. nigrostriata, H. sagamiensis, H. kanga, Jorunna funebris, Phyllidia ocellata, P. polkadotsa, Phyllidiopsis phiphiensis, and Elysia marginata. Remarkably, 13 of these heterobranchs species are documented for the first time in the Andhra Pradesh region, with 12 belonging to the order Nudibranchia and one to the superorder Sacoglossa. The manuscript provides a comprehensive analysis of morphometric characteristics, detailed descriptions, photography, and distribution trends of 19 heterobranchs species, as well as a comprehensive literature record of sea slugs found in Andhra Pradesh, India. Sea slugs, being the butterflies of the ocean, are a great part of the ecosystem, although based on economic valuation, they are regarded as a low-value bycatch, trash. The bottom trawl is one of the major threats to the habitat destruction for these animals. Thus, the habitats along the Andhra coastline should be known so that fishing activities in these parts could be restricted for the better survival of sea slugs.